2014
DOI: 10.1142/s1793545813500673
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation of GLUT4 translocation promotes glucose uptake via PI3-K/Akt2 signaling in 3T3-L1 adipocytes

Abstract: Insulin resistance is a hallmark of the metabolic syndrome and type 2 diabetes. Dysfunction of PI-3K/Akt signaling was involved in insulin resistance. Glucose transporter 4 (GLUT4) is a key factor for glucose uptake in muscle and adipose tissues, which is closely regulated by PI-3K/Akt signaling in response to insulin treatment. Low-power laser irradiation (LPLI) has been shown to regulate various physiological processes and induce the synthesis or release of multiple molecules such as growth factors, which (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Kenji Ryotokuji et al [39] have shown that pinpoint plantar longwavelength infrared light irradiation (PP-LILI) can normalize blood glucose levels by reducing stress hormones and by improving insulin sensitivity. Our recent study confirmed that He-Ne laser can promote glucose uptake of 3T3-L1 adipocytes through activating PI3-K/Akt/ GLUT4 pathway [24]. Nevertheless, whether LPLI could ameliorate lipid metabolic disorders remains unclear.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Kenji Ryotokuji et al [39] have shown that pinpoint plantar longwavelength infrared light irradiation (PP-LILI) can normalize blood glucose levels by reducing stress hormones and by improving insulin sensitivity. Our recent study confirmed that He-Ne laser can promote glucose uptake of 3T3-L1 adipocytes through activating PI3-K/Akt/ GLUT4 pathway [24]. Nevertheless, whether LPLI could ameliorate lipid metabolic disorders remains unclear.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, growing evidences have shown that LPLI activates RTKs and triggers its downstream effectors, such as Ras, PKC, and PI3-K/Akt [19,23]. Recent study has demonstrated that LPLI promotes glucose uptake through activation of PI-3K/Akt2/GLUT4 pathway in 3T3-L1 adipocytes [24]. The effects of LPLI on energy expenditure in adipocytes may provide potential for improving metabolic disorders in insulin-resistant condition.…”
Section: Introductionmentioning
confidence: 99%